Food System Monitoring navigating a data-driven future (WP4): Webniar - Jimenez, Daniel; Garcia, Gustavo; Castillo, Johana M.; Manners, Rhys; Storr, Samuel (2023)
The webinar, hosted by the digital innovation initiative under work package 4, focused on Food System Monitoring and featured a panel of experts who shared insights from their work in various countries. The speakers highlighted the benefits of digital transformation in agriculture, particularly in regions with limited traditional information sources. Digital tools like phone surveys, remote sensing data, and government data through web platforms enable the collection of more precise data, allowing for the identification of patterns and trends, predictive analytics, and early warning systems. These advancements are crucial for providing stakeholders with a clear and robust understanding of agri-food systems, especially in regions facing poverty and nutrition challenges.